Online consumer reviews and their influence on consumer buying behaviour – a study with reference to gujarat - Pruthvirajsinh n. Rathod (Journal of Informatics Education and Research, 2025)
The rapid growth of information technology and widespread adoption of e-commerce platforms have significantly changed the decision-making patterns of consumers across india. One of the most impactful developments in this transformation is the growing credibility and usage of online consumer reviews (ocrs) as a decision support tool. Ocrs allow consumers to share product experiences, rate products and services, offer feedback, and influence future buyers. This study investigates the role and impact of online consumer reviews on buying behaviour among customers in gujarat, a rapidly expanding digital market supported by large-scale internet penetration, improving digital literacy, and increasing dependence on e-retail platforms. The purpose of this research is to analyse how electronic word-of-mouth influences consumer perception, evaluation, and purchase intentions with particular reference to consumers residing in gujarat. A primary survey was conducted with a sample size of 300 respondents belonging to various cities of gujarat, including ahmedabad, surat, vadodara, bhavnagar, jamnagar, and rajkot. Exploratory research design was used at the preliminary stage through interviews and informal discussions to understand respondent orientation, followed by a structured questionnaire survey. Data analysis was carried out using karl pearson correlation and regression, with the aim of testing the significance and strength of relationships among variables such as helpfulness of reviews, review credibility, review depth, star ratings, and consumer purchase decisions. This study concludes that online consumer reviews have become one of the most trusted forms of information for digital buyers in gujarat, significantly influencing brand perception, service choice, product evaluation, and willingness to purchase.